Tidal range electricity generation: A comparison between estuarine barrages and coastal lagoons. Issue 11 (November 2022) - Vandercruyssen, David; Baker, Simon; Howard, David; Aggidis, George
Abstract: The potential power from coastal tidal range is becoming better appreciated due to the need to mitigate global warming. Great Britain (GB) is ideally situated to exploit tidal power but currently has no operational systems. Historically, estuaries have been proposed as sites for barrages, but more recently coastal lagoons are favoured due to a lower environment impact. To contrast the differences between barrages and lagoons two potential schemes are analysed using the Lancaster 0-D Tidal Range Model. Both schemes were analysed with a range of turbine numbers and generator ratings. The schemes are compared in terms of energy generation, flood protection, navigation, and selected environmental impacts. The analysis indicates that the schemes are not categorically different, characterised by the shape and alignment of the impoundment. Barrages impoundments across estuaries are generally shorter than lagoons impounding similar volumes, with lower civil engineering costs. Whilst estuaries tend to have slightly higher tidal ranges, they also create unique ecological conditions with diverse natural ecosystems that are increasingly valued. The analysis shows that 2-way generation and pumping can match the full tidal range and help preserve inter-tidal areas. Abstract : Renewable energy; Tidal range; Tidal barrage; Morecambe bay barrage; North Wales lagoon. Highlights: Estuary barrage and coastal lagoon energy generation and environmental impact. Two-way generation & pumping limits prevents loss of intertidal area. Flood protection from storm surges and sea-level rise. Annual electricity generation for various generator ratings and sluice ratios. Comparison of two case study sites with identical intertidal range.